2007
DOI: 10.1038/sj.jes.7500599
|View full text |Cite
|
Sign up to set email alerts
|

Daily mercury intake in fish-eating populations in the Brazilian Amazon

Abstract: Although high levels of fish consumption and bioindicators of mercury exposure have been reported for traditional populations in the Amazon, little is known about their actual daily intake of Hg. Using an ecosystem approach, calculate daily mercury intake in adult fish-eaters, examine the relations between mercury intake and bioindicators of exposure and the factors that influence these relations. A cross-sectional dietary survey on fish and fruit consumption frequency was carried out with 256 persons from six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 70 publications
1
55
3
3
Order By: Relevance
“…The results of the present study are in agreement with earlier findings that show high levels of Hg exposure in the Amazon region (Dórea et al 2005, Pinheiro et al 2006Passos et al 2008). It is notable that high variations in Hg levels were found among participants in the present study; for example, in total blood, Hg levels ranged from 4.7 to 122 μg/L, while in hair the variation was from 1 to GST POLYMORPHISMS AND METHYLMERCURY METABOLISM 965 FIGURE 3.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study are in agreement with earlier findings that show high levels of Hg exposure in the Amazon region (Dórea et al 2005, Pinheiro et al 2006Passos et al 2008). It is notable that high variations in Hg levels were found among participants in the present study; for example, in total blood, Hg levels ranged from 4.7 to 122 μg/L, while in hair the variation was from 1 to GST POLYMORPHISMS AND METHYLMERCURY METABOLISM 965 FIGURE 3.…”
Section: Discussionsupporting
confidence: 82%
“…In an earlier study, Passos et al (2008) demonstrated that fish consumption was related to Hg concentrations in the same population. In the present study, fish intake ranged between one and four portions per day, and this can also be related to variations in metal concentrations in the blood stream and hair.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Fréry et al 34 , em períodos de abundância o consumo diário de peixe pode alcançar 600g. Em crianças de até 5 anos na região do rio Madeira, Boischio & Henschel 31 estimaram uma ingestão diária de Hg de 6.4ugkg -1 , e no Tapajós, Passos et al 35 observaram uma ingestão diária em adultos variando de 0 a 11.8µgkg -1 , com média de 0.92µgkg -1 .…”
Section: Resultsunclassified
“…This type of exposure is much more common in humans. Recently, Passos et al (2008) described the typical daily intake of MeHg in traditional riparian populations of the Tapajos River in Brazil as being about 70 lg/day. This level is much lower than that usually evaluated adverse effects of MeHg in animal models .…”
Section: Discussionmentioning
confidence: 99%